Indonesian tourism infrastructure competitiveness - Ernawati, Ernawati (Universitas Muhammadiyah Pontianak, 2018)
Tourism infrastructure is the pillars that undermine the competitiveness of Indonesiantourism. This study aims to determine the factors that weaken the competitiveness ofthe tourism infrastructure in Indonesia. The data were analyzed descriptively.Indicators of the strength and weakness of infrastructure competitiveness aredetermined by performing a comparative value that obtained from everycompetitiveness indicator published by the World Economic Forum period of 2015,against four major competing countries in ASEAN (Singapore, Thailand, Malaysia,and the Philippines). The results showed that some of the indicators that weakens thecompetitiveness of Indonesia's infrastructure namely: quality of air transportinfrastructure, international airline seat, quality of roads, quality of port infrastructure,and the ATMs accepting visa cards. Even the presence of major car rental companiesand extension of business trips recommended placed Indonesia in the final sequenceof the four major competitor countries in Southeast Asia. Indonesia only has three ofstrength indicator of tourism infrastructure, consists of the domestic airline seat,quality of railroad infrastructure and the quality of ground transport network.